2016
DOI: 10.3847/0004-637x/819/1/84
|View full text |Cite
|
Sign up to set email alerts
|

The Inner Edge of the Habitable Zone for Synchronously Rotating Planets Around Low-Mass Stars Using General Circulation Models

Abstract: Terrestrial planets at the inner edge of the habitable zone (HZ) of late-K and M-dwarf stars are expected to be in synchronous rotation, as a consequence of strong tidal interactions with their host stars. Previous global climate model (GCM) studies have shown that, for slowly rotating planets, strong convection at the substellar point can create optically thick water clouds, increasing the planetary albedo, and thus stabilizing the climate against a thermal runaway. However these studies did not use self-cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
264
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(286 citation statements)
references
References 35 publications
18
264
2
1
Order By: Relevance
“…This heating forms a thermal inversion, which is stable against deep convection and thus prohibits the formation of convective clouds (See section 3.3 for more discussion). Kopparapu et al (2016) found that the above-described radiative-convective transition also occurs on slow and synchronously rotating Earth-like planets, which are expected around low mass stars. While rapidly rotating planets can maintain climatological stability beyond this transition due to cloud adjustments in the upper atmosphere, this transition is catastrophic for planets located near the inner edge of the HZ around low mass stars.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This heating forms a thermal inversion, which is stable against deep convection and thus prohibits the formation of convective clouds (See section 3.3 for more discussion). Kopparapu et al (2016) found that the above-described radiative-convective transition also occurs on slow and synchronously rotating Earth-like planets, which are expected around low mass stars. While rapidly rotating planets can maintain climatological stability beyond this transition due to cloud adjustments in the upper atmosphere, this transition is catastrophic for planets located near the inner edge of the HZ around low mass stars.…”
Section: Introductionmentioning
confidence: 99%
“…It is also useful in determining the occurrence of potentially habitable planets in our galaxy, as was done with Kepler data. Several groups have studied the limits of the mainsequence HZ (Kasting et al 1993;Pierrehumbert & Gaidos 2011;Kopparapu et al 2013; Leconte et al 2013a;Yang et al 2013;Barnes et al 2013;Zsom et al 2013;Kopparapu et al 2014;Wolf & Toon 2014;Yang et al 2014a;Way et al 2015;Wolf & Toon 2015;Leconte et al 2015;Godolt et al 2015;Kopparapu et al 2016;Haqq-Misra et al 2016;Ramirez & Kaltenegger 2017;Salameh et al 2017) using both 1-D and 3-D climate models, and corresponding climate transitions that planets undergo at these limits. Many of these models assume water-rich (∼ 1 Earth ocean) planets, which is reasonable if one wants to study the surface habitability of a planet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it shows that if the top-of-atmosphere ice/ocean albedo contrast is smaller, a planet is less likely to experience a snowball bifurcation (C * increases). This is important because tidally locked terrestrial planets should have massive cloud decks on their day sides (Yang et al 2013;Way et al 2015;Kopparapu et al 2016;Salameh et al 2017). This should tend to increase the top-ofatmosphere albedo over open ocean regions, making the effective albedo contrast between ocean and ice/snow smaller.…”
Section: Tidally Locked Planetmentioning
confidence: 99%
“…M-dwarfs are the most common type of star in the galaxy, and in recent years there has been a large amount of work on whether tidally locked planets in the habitable zone of M-dwarf stars could host life (e.g., Joshi et al 1997;Segura et al 2005;Merlis & Schneider 2010;Kite et al 2011;Wordsworth et al 2011;Pierrehumbert 2011;Yang et al 2013;Leconte et al 2013;Menou 2013;Yang et al 2014;Kopparapu et al 2016;Turbet et al 2016;Ribas et al 2016;Barnes et al 2016;Meadows et al 2016;Wolf 2017;Bolmont et al 2017). This topic is particularly timely given the recent discoveries of likely terrestrial planets in the habitable zones of three M-dwarfs within 40 light years of Earth (TRAPPIST-1e, Proxima Centauri b, and LHS 1140b, Anglada-Escudé et al 2016;Gillon et al 2017;Dittmann et al 2017).…”
Section: Introductionmentioning
confidence: 99%